Demographic, epidemiological and nutritional profile of elders in home enteral nutritional therapy in Distrito Federal, Brazil. - Salomon Zaban, Ana Lúcia; Carvalho Garbi Novaes, Maria Rita (Investigación Clínica, 2013)
According to statistical projections of the World Health Organization, during the period between 1950 and 2025, the group of elderly in Brazil will have increased 15 times. Chronic-degenerative diseases are the illnesses that most affect the elderly population, directly related to the growing demand for Enteral Nutrition Therapy. The objective of this study was to analyze the demographic, epidemiological and nutritional profile of elderly patients assisted at the public hospitals in the Home Enteral Nutrition Therapy Program, of the State Health Department of Distrito Federal. This is a retroprospective, cross-sectional and analytical study, based on primary data, which enrolled 141 elderly patients who were prescribed home enteral nutrition. The collected variables corresponded to age, gender, clinical diagnosis, enteral route and nutritional status at the beginning of Home Enteral Nutrition Therapy. The association between variables was analyzed through the t-Student and chi-square tests, with a significance level of 0.05 and a Confidence Interval (CI) of 95%. There was a higher number of female patients (53.9%) when compared to male (46.1%), average age 75.82 years old for both groups. The most prevalent diseases were cerebro-vascular accident sequels and cancer (42.6% and 22.7% respectively). It was observed a prevalence of malnutrition equal to 69.7%, independent of age and gender. The most used enteral route was the nasal. Though Brazilian policies concerning assistance to the elderly have advanced during the last few years, the need for public policies for nutritional recovery of such patients persists, to promote a better quality of life for them.